Can concomitant above-knee femoropopliteal bypass with artificial graft affect the outcome of femorofemoral bypass with artificial graft?. (December 2022) - Kim, In-Sub; Cha, Jaehyung; Jo, Won-Min
Objectives: Few have studied the effect of concomitant femoropopliteal (FEM-POP) bypass surgery on the outcome of femorofemoral (FEM-FEM) bypass in patients with peripheral arterial disease (PAD). This study was aimed to analyze the risk relationship of concomitant FEM-POP bypass on the patency of FEM-FEM bypass. Methods: From March 2009 to April 2020, a total of 27 patients who underwent FEM-FEM bypass surgery using polytetrafluoroethylene grafts were retrospectively analyzed according to concomitant FEM-POP bypass surgery. The mean follow-up duration was 38.20 ± 34.56 months. Results: The overall primary patency of the FEM-FEM bypass grafts in all 27 patients was 83.7, 78.5, and 72.0 at one, two, and 3 years, respectively. The overall limb salvage rate was 100, 94.1, and 86.9 at one, two, 3 years, respectively. Among them, ten patients underwent FEM-FEM bypass only (group 1). The other 17 patients needed a concomitant FEM-POP bypass and these patients were classified into three groups (group 2, ipsilateral FEM-POP, n = 5; group 3, crossover FEM-POP, n = 6; and group 4, bilateral FEM-POP, n = 6) The comparison of the primary patency of group 1 with the concomitant FEM-POP groups (sum of groups 2, 3, and 4, that is, group 5, n = 17) revealed a statistically significant improved patency for FEM-FEM bypasses not requiring concomitant infra-inguinal bypass ( p = .036). Among the concomitant FEM-POP groups, group 2 had the lowest primary patency of the FEM-FEM bypass significantly ( p = 0.07). The limb salvage rate of group 4 was significantly low. Conclusions: A concomitant FEM-POP bypass influenced the outcome of FEM-FEM bypass surgery. In conclusion, compromised infra-inguinal runoff at either extremity requiring concomitant FEM-POP bypass significantly worsens long-term FEM-FEM bypass patency. In addition, a concomitant bilateral FEM-POP bypass is a risk factor affecting the limb salvage rate in FEM-FEM bypass.